A simple and efficient fluorescent labeling method in Staphylococcus aureus for real-time tracking of invasive bacteria - Liu, Fei; Chen, Sijie; Zou, Yingxin; Jiao, Yong; Tang, Ying (Frontiers in Microbiology, 2023)
Bacterial fluorescent labeling is a powerful tool for the diagnosis and treatment of bacterial infections. Here, we present a simple and efficient labeling strategy for Staphylococcus aureus. Intracellular labeling of bacteria was achieved by heat shock using Cyanine 5.5 (Cy5.5) near-infrared-I dyes in S. aureus (Cy5.5@S. aureus). Several key factors, such as Cy5.5 concentration and labeling time, were systematically evaluated. Further, the cytotoxicity of Cy5.5 and the stability of Cy5.5@S. aureus was evaluated by flow cytometry, inverted fluorescence microscopy, and transmission electron microscopy. In addition, Cy5.5@S. aureus were used to explore the phagocytic behavior of RAW264.7 macrophages. These results proved that Cy5.5@S. aureus had a uniform fluorescence intensity and high luminance; additionally, our method had no significant adverse effects on S. aureus compared to unlabeled S. aureus infections. Our method provides researchers with a useful option for analyzing the behavior of S. aureus as an infectious agent. This technique can be broadly applied to study host cell–bacteria interactions at the molecular level, and to in vivo tracing of bacterial infections.